Pulmonary Rehabilitation: A Review of the Recent Literature - Goldstein, R.; Hill, Kylie; Brooks, D.; Dolmage, T. (American College of Chest Physicians, 2012)
Pulmonary rehabilitation (PR) is an evidence-based, multidisciplinary, comprehensive intervention that can be integrated into the management of individuals with chronic lung disease. It aims to reduce symptoms, optimize function, increase participation in daily life, and reduce health-care resource utilization. In this review, we summarize the new developments in PR over the past 5 years. Issues related to patient assessment include a comparison of cycle- and walking-based measures of exercise capacity, the emergence of multidimensional indices, the refinement of the minimal clinically important difference, and the importance of assessing physical activity. Issues related to exercise training focus on strategies to optimize the training load. We also comment on the acquisition of self-management skills, balance training, optimizing access, and maintaining gains following completion of PR.